Modern Electrochemical Methods for Monitoring of Chemical Carcinogens - J. Zima; J. Moreira; J. Barek (Sensors, 2005)
This contribution is based on our presentation at the 1st International Symposiumon Sensor Science, Paris, 16-20 June 2003. It presents recent results regarding theelectrochemical determination of submicromolar and nanomolar concentrations of variouscarcinogenic substances (nitrated polycyclic aromatic hydrocarbons, heterocycliccompounds, azo compounds, aromatic amino compounds, etc.) using both traditional(classical dropping mercury electrode, static mercury drop electrode, hanging mercury dropelectrode) and non-traditional types of electrodes (solid amalgam electrodes, carbon pasteelectrodes, platinum tubular electrodes).